Analysis of Student Learning Media Needs in Object-Based Programming (PBO) Subjects - Wiguna, Akbar; Astuti, Cindy Cahyaning; Hasanah, Fitria Nur; Sri Untari, Rahmania (Gammath : Jurnal Ilmiah Program Studi Pendidikan Matematika, 2024)
Object-Oriented Programming (OOP) is a fundamental course in computer science, particularly in software and application design. However, programming is often perceived as challenging by many students. Effective learning should stimulate creativity, actively engage students, achieve learning objectives effectively, and occur in conducive environments. One strategy to achieve this is by utilizing learning media tailored to students' needs. This study aims to analyze university students' needs in learning Object-Oriented Programming. A qualitative approach was employed using a case study method. The study examined students' perceptions of pair programming in OOP courses at the University of Muhammadiyah Sidoarjo (UMSIDA) within the Information Technology Education (PTI) program. The findings indicate that students predominantly use PCs or laptops for programming and require digital learning media to enhance their learning experience. They prefer materials that provide clear instructions and commands and are more comfortable with media that integrate text and visual elements. The analysis reveals a need for e-modules designed specifically for laptops/PCs, incorporating images, text, and detailed instructions for effective programming learning.